2008
DOI: 10.1142/s0218301308009860
|View full text |Cite
|
Sign up to set email alerts
|

SHAPE PHASE TRANSITIONS AND POSSIBLE E(5) SYMMETRY NUCLEI FOR Ti ISOTOPES

Abstract: Relativistic mean field theory is used to produce potential energy surfaces (PESs) for Ti isotopes. The relatively flat PESs suggest that 48, 52, 60 Ti , being on the way from vibrations to γ-unstable behavior, are the possible examples with the transitional dynamical symmetry E(5). Especially for 48 Ti , PES shows that it is a better candidate with E(5) symmetry. These conclusions are supported by the experimental data via the observed ratios of excitation energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…This elicites a very large β 2 deformation with the formula. However, in medium-mass and heavy region usage of the formula is siutable [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This elicites a very large β 2 deformation with the formula. However, in medium-mass and heavy region usage of the formula is siutable [30].…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, 148,150,152 Sm and 128,130,132,134 Ce have been suggested as an example of the possible critical-point nuclei with X(5) symmetry. Beside, Ti isotopes have been examined in the HFB method [29] and RMF model [30] to investigate the critical-point nuclei. In these studies, 48,52,60 Ti and 46,52,60 Ti have been found as to be the possible candidate critical-point nuclei with E(5) symmetry in the RMF model and HFB method, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Bu simetriler deneysel olarak Ba-134 [8] ve Sm-152 [9] çekirdeklerinin spektrumlarından belirlendi. Genellikle QPT'ler geometrik modellerle [10][11][12] ve cebirsel modellerle [12][13][14][15][16][17][18][19][20] çalışılmasına rağmen teorik çalışmalar RMF modeli [21][22][23][24][25] ve HartreeFock-Bogoliubov (HFB) modeli [3,26,27] ile de gerçekleştirilmiştir. Bu çalışmalarda hem RMF ve hem de HFB modelinde kısıtlı kuadrupol moment değerleri ile elde edilen potansiyel enerji eğrileri hesaplanmaktadır (PEC).…”
Section: Introductionunclassified
“…Also, phenomenological mean field models (e.g, Hartree-Fock-Bogoliubov (HFB) method [7,8] and relativistic mean field (RMF) model [9,10,11]) have been used to investigate the critical-point nuclei with E (5) or X (5) symmetry in Ref. [12,13,14,15,16,17,18,19,20]. In these studies, potential energy curves (PECs) obtained from quadrupole constrained calculations have been used for describing the possible critical-point nuclei.…”
Section: Introductionmentioning
confidence: 99%